Analysis of Maritime Welding Policy in the Development of Global Hub Bandar Kayangan in North Lombok, Indonesia - Joko Susilo Raharjo; Ermaya Suradinata; Sampara Lukman; Lalu Wildan (International Journal of Science and Society, 2019)
This study aims to find the development of new models, using qualitative research designs with descriptive research types. The research informants were carried out by means of interviews, observations and literature studies as the techniques used in collecting data. While data reduction, data retrieval and conclusion drawing became the technical analysis of qualitative data used in this study. The analysis used in this study is an analysis of the implementation of the public policy model of Grindle (1980) and continued with analysis of ASOCA strategies. The results of this study are 1) Implementation of the global development policy Bandar Kayangan Hub can not be implemented optimally 2) Required strategies for problem solving in decision making. From the results of the analysis of the implementation of public policy based on Empirical Findings of ASOCA strategy analysis, a new concept of implementation strategy model 7 P JSRW was obtained, namely: 1) Government role (delegation process), 2) Zoning regulations, 3) Media role in making public opinion 4) The use of local labor, 5) The role of universities in printing experts, 6) Business actors (attracting investors) 7) Fair legal enforcement.